2022
DOI: 10.3390/nu14102052
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels as an Important Predictor for Type 2 Diabetes Mellitus and Weight Regain Post-Sleeve Gastrectomy

Abstract: Weight Loss Surgery (WLS), including sleeve-gastrectomy (SG), results in significant weight loss and improved metabolic health in severe obesity (BMI ≥ 35 kg/m2). Previous studies suggest post-operative health benefits are impacted by nutrient deficiencies, such as Vitamin D (25(OH)D) deficiency, while it is currently unknown whether nutrient levels may actually predict post-surgery outcomes. As such, this study investigated whether 25(OH)D levels could predict metabolic improvements in patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Therefore, around one-third of the patients opt for alternative therapies [5]. Since vitamin D deficiency is a common condition [6][7][8][9] associated with cardiovascular disease (CVD) [10], cancer [11], insulin resistance [12][13][14], and other chronic diseases [15], investigators have sought to identify possible associations of vitamin D deficiency with IBS. Therefore, studies have shown an improvement of IBS symptoms with the administration of vitamin D [16,17], an agent playing a critical role in calcium and phosphorous metabolism and homeostasis as well as anti-inflammatory and immunomodulatory activities [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, around one-third of the patients opt for alternative therapies [5]. Since vitamin D deficiency is a common condition [6][7][8][9] associated with cardiovascular disease (CVD) [10], cancer [11], insulin resistance [12][13][14], and other chronic diseases [15], investigators have sought to identify possible associations of vitamin D deficiency with IBS. Therefore, studies have shown an improvement of IBS symptoms with the administration of vitamin D [16,17], an agent playing a critical role in calcium and phosphorous metabolism and homeostasis as well as anti-inflammatory and immunomodulatory activities [18].…”
Section: Introductionmentioning
confidence: 99%